Positive biodiversity-productivity relationship predominant in global forests - Jingjing, L.; Crowther, T.W.; Picard, N.; Wiser, Susan K.; Mo, Z.; Alberti, G.; Schulze, Ernst-Detlef; McGuire, A.D.; Bozzato, F.; Pretzsch, H.; Miguel, S. de; Paquette, A.; et al. (American Association for the Advancement of Science, 2016)
The relationship between biodiversity and ecosystem productivity has been explored in detail in herbaceous vegetation, but patterns in forests are far less well understood. Liang et al. have amassed a global forest data set from >770,000 sample plots in 44 countries. A positive and consistent relationship can be discerned between tree diversity and ecosystem productivity at landscape, country, and ecoregion scales. On average, a 10% loss in biodiversity leads to a 3% loss in productivity. This means that the economic value of maintaining biodiversity for the sake of global forest productivity is more than fivefold greater than global conservation costs.Science , this issue p. 196